Complementation of nitrogen-regulatory (ntr-like) mutations in Rhodobacter capsulatus by an Escherichia coli gene: cloning and sequencing of the gene and characterization of the gene product. - Allibert, P (1987)
In vivo genetic engineering by R' plasmid formation was used to isolate an Escherichia coli gene that restored the Ntr+ phenotype to Ntr- mutants of the photosynthetic bacterium Rhodobacter capsulatus (formerly Rhodopseudomonas capsulata; J. F. Imhoff, H. G. Trüper, and N. Pfenning, Int. J. Syst. Bacteriol. 34:340-343, 1984). Nucleotide sequencing of the gene revealed no homology to the ntr genes of Klebsiella pneumoniae. Furthermore, hybridization experiments between the cloned gene and different F' plasmids indicated that the gene is located between 34 and 39 min on the E. coli genetic map and is therefore unlinked to the known ntr genes. The molecular weight of the gene product, deduced from the nucleotide sequence, was 30,563. After the gene was cloned in an expression vector, the gene product was purified. It was shown to have a pI of 5.8 and to behave as a dimer during gel filtration and on sucrose density gradients. Antibodies raised against the purified protein revealed the presence of this protein in R. capsulatus strains containing the E. coli gene, but not in other strains. Moreover, elimination of the plasmid carrying the E. coli gene from complemented strains resulted in the loss of the Ntr+ phenotype. Complementation of the R. capsulatus mutations by the E. coli gene therefore occurs in trans and results from the synthesis of a functional gene product.